2016
DOI: 10.4103/2229-3485.173775
|View full text |Cite
|
Sign up to set email alerts
|

Publication speed and advanced online publication: Are biomedical Indian journals slow?

Abstract: Objective:The aim of this study was to identify the publication speed (peer review time and publication time) of biomedical Indian journals and identify the journals having the facility of advance online publication (AOP).Materials and Methods:Biomedical Indian journals were identified from the Journal Citation Report of 2013. Thirty original articles published between January 2012 and June 2014 were systematically selected from each journal. Information about the date of submission, revision, and acceptance w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 8 publications
2
27
0
2
Order By: Relevance
“…Thanks to the spread of internet in the last decades, researchers were given the opportunity to submit their research online, and it has been shown that online submission of manuscripts was more efficient than paper submission in terms of acceptance time (Govender et al 2008). We found that online publication was more efficient in terms of publication General Adjusted difference in median time between impact factor > 2.2 and < 1.6: − 85.7 days; between impact factor > 2.2 and 1.6-2.2: − 101.3 days § Not selected in the multivariate model and total delay times, confirming studies in ophthalmology, nursing and biomedical Indian journals (Chen et al 2013;Palese et al 2013;Shah et al 2016). The fact that online publication was not linked to acceptance time in our study is a logical finding, since online publication should only affect the publication and not the peer review process.…”
Section: Comparison With Existing Literaturesupporting
confidence: 60%
See 3 more Smart Citations
“…Thanks to the spread of internet in the last decades, researchers were given the opportunity to submit their research online, and it has been shown that online submission of manuscripts was more efficient than paper submission in terms of acceptance time (Govender et al 2008). We found that online publication was more efficient in terms of publication General Adjusted difference in median time between impact factor > 2.2 and < 1.6: − 85.7 days; between impact factor > 2.2 and 1.6-2.2: − 101.3 days § Not selected in the multivariate model and total delay times, confirming studies in ophthalmology, nursing and biomedical Indian journals (Chen et al 2013;Palese et al 2013;Shah et al 2016). The fact that online publication was not linked to acceptance time in our study is a logical finding, since online publication should only affect the publication and not the peer review process.…”
Section: Comparison With Existing Literaturesupporting
confidence: 60%
“…We found a weak association with impact factor, journals with higher impact factor being more likely to have shorter total delay times. There is conflicting evidence in the literature on this topic: Kalcioglu et al (2015) showed quite the opposite, since otorhinolaryngology journals with higher impact factor were more likely to have longer acceptance and publication times, whereas two other studies targeting ophthalmology and biomedical Indian journals found no association (Chen et al 2013;Shah et al 2016). Our finding might be explained by the fact that high-impact journals in general have more resources; these resources may be partly used to identify the problems encountered in the peer-review process and to develop strategies to improve the publication speed.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Many studies evaluated the publication process times in different biomedical areas and geographic regions, reporting acceptance lag (i.e., time from submission date to acceptance date) of usually over 100 days. [8][9][10][11][12][13][14] Pharmacy Practice reported a first response time after peer review comments of 92 days (SE=5.7) in 2018. 15 We are happy to announce that Pharmacy Practice first response time for original research articles accepted decreased to 80 days (SE=3.8) in 2019, with an acceptance lag of 124 days (SE=5.0).…”
Section: 7mentioning
confidence: 99%